Structural basis for the molecular evolution of SRP-GTPase activation by protein - Bange, Gert; Kümmerer, Nico; Grudnik, Przemyslaw; Lindner, Robert; Petzold, Georg; Kressler, Dieter; Hurt, Ed; Wild, Klemens; Sinning, Irmgard (Nature structural & molecular biology, 2011)
SRP-type GTPases deviate from other GTPases in that they are not activated by GTPase-activating proteins (GAPs). New studies show that the MinD-type protein YlxH activates the SRP-GTPase FlhF, which is involved in flagellar biosynthesis. The crystal structure of the Bacillus subtilis FlhF-effector complex reveals the mechanism of activation, the general concept of which may also apply to RNA-mediated activation of the SRP-GTPases Ffh and FtsY.